A Chomsky-Schützenberger-Stanley type characterization of the class of slender context-free languages - Dömösi, Pál; Okawa, Satoshi (Acta Cybernetica, 2001)
Slender context-free languages have a complete algebraic characterization by L. Ilie in [13]. In this paper we give another characterization of this class of languages. In particular, using linear Dyck languages instead of unrestricted ones, we obtain a Chomsky-Schützenberger-Stanley type characterization of slender context-free languages.